THE EFFECT OF THE USE OF PICTURE DOMINO CARDS MEDIA TOWARD HEARING IMPAIRMENT STUDENT’S COMPETENCE IN WRITING SIMPLE SENTENCES FOR STUDENT - Nurvidia Anassyah; M Shodiq AM (Department of Special Education, 2016)
This research was aimed at describing: (1) the students’ competence before being given intervention with pictorial domino cards, (2) the students’ competence after being given intervention with pictorial domino cards, and (3) the effect of picture domino cards toward the students’ competence in writing simple sentences. The research method used was experimental method using Single Subject Research (SSR) with A-B-A design. The research results showed that the overlap percentage was 0%, it’s mean that there was an effect of the usage of pictorial domino cards toward the improvement of writing simple sentences competence of a student with hearing impairment. Penelitian ini bertujuan untuk mendeskripsikan: 1) kemampuan peserta didik sebelum diberikan intervensi menggunakan kartu domino kata bergambar, 2)kemampuan peserta didik setelah diberikan intervensi menggunakan kartu domino kata bergambar, dan 3) pengaruh kartu domino kata bergambar terhadap kemampuan menulis kalimat sederhana. Metode penelitian yang digunakan adalah metode eksperimen dengan menggunakan Single Subject Reseach (SSR) desain A-B-A. Hasil penelitian menunjukan bahwa presentase overlap sebesar 0%, yang berarti terdapat pengaruh penggunaan media kartu domino kata bergambar terhadap peningkatan kemampuan menulis kalimat sederhana peserta didik tunarungu.